An Old Man on the Frontier Loses His Horse. - Tung, Angela (Bellingham Review)
Presents a personal narrative which explores the author's experience of being a young woman of Chinese descent who dates and marries a Korean man named Joe, of feeling disapproval from a mother-in-law who believes in luck and fortune, and of getting a divorce after her husband has an affair.